Ocular findings in 22q11.2 deletion syndrome: A systematic literature review and results of a Dutch multicenter study. Issue 2 (12th November 2021) - von Scheibler, Emma N. M. M.; van der Valk Bouman, Emy S.; Nuijts, Myrthe A.; Bauer, Noël J. C.; Berendschot, Tos T. J. M.; Vermeltfoort, Pit; Bok, Levinus A.; van Eeghen, Agnies M.; Houben, Michiel L.; van Amelsvoort, Thérèse A. M. J.; Boot, Erik; van Egmond‐Ebbeling, Michelle B.
Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is a multisystem disorder with an estimated prevalence of 1:3000 live births. Manifestations show a marked variability in expression and include speech‐ and language delay, intellectual disability, and neuropsychiatric disorders. We aim to provide an overview of ocular findings in 22q11.2DS in order to optimize recommendations for ophthalmic screening. We combined results from a systematic literature review with results from a multicenter cross‐sectional study of patients with 22q11.2DS who were assessed by an ophthalmologist. Our systematic literature search yielded four articles, describing 270 patients. We included 132 patients in our cross‐sectional study (median age 8.9 [range 0–56] years). Most reported ocular findings were retinal vascular tortuosity (32%–78%), posterior embryotoxon (22%–50%), eye lid hooding (20%–67%), strabismus (12%–36%), amblyopia (2%–11%), ptosis (4%–6%), and refractive errors, of which hyperopia (6%–48%) and astigmatism (3%–23%) were most common. Visual acuity was (near) normal in most patients (91%–94%). Refractive errors, strabismus, and amblyopia are treatable conditions that are frequently present in patients with 22q11.2DS and should be corrected at an early stage. Therefore, in 22q11.2DS, we recommend ophthalmic and orthoptic screening at the age of 3 years or at diagnosis, and a low‐threshold referral in adults.